Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
[tex](x-h)^2+(y-k)^2=r^2[/tex]
(h,k) - the center
r - the radius
[tex]4x^2+4y^2+4x-16y-19=0 \ \ \ |\div 4 \\ x^2+y^2+x-4y-\frac{19}{4}=0 \\ x^2+x+\frac{1}{4}+y^2-4y+4-\frac{19}{4}-\frac{1}{4}-4=0 \\ (x+\frac{1}{2})^2+(y-2)^2-\frac{20}{4}-4=0 \\ (x+\frac{1}{2})^2+(y-2)^2-5-4=0 \\ (x+\frac{1}{2})^2+(y-2)^2-9=0 \\ (x+\frac{1}{2})^2+(y-2)^2=9 \\ (x+\frac{1}{2})^2+(y-2)^2=3^2[/tex]
The center - [tex](-\frac{1}{2},2)[/tex]
The radius - [tex]3[/tex]
(h,k) - the center
r - the radius
[tex]4x^2+4y^2+4x-16y-19=0 \ \ \ |\div 4 \\ x^2+y^2+x-4y-\frac{19}{4}=0 \\ x^2+x+\frac{1}{4}+y^2-4y+4-\frac{19}{4}-\frac{1}{4}-4=0 \\ (x+\frac{1}{2})^2+(y-2)^2-\frac{20}{4}-4=0 \\ (x+\frac{1}{2})^2+(y-2)^2-5-4=0 \\ (x+\frac{1}{2})^2+(y-2)^2-9=0 \\ (x+\frac{1}{2})^2+(y-2)^2=9 \\ (x+\frac{1}{2})^2+(y-2)^2=3^2[/tex]
The center - [tex](-\frac{1}{2},2)[/tex]
The radius - [tex]3[/tex]
[tex] 4x^2+4y^2+4x-16y-19=0 \\
4x^2+4x+1+4y^2-16y+16-36=0\\
(2x+1)^2+(2y-4)^2=36[/tex]
center - [tex](-1,4)\\ [/tex]
[tex]r=\sqrt{36}=6[/tex]
center - [tex](-1,4)\\ [/tex]
[tex]r=\sqrt{36}=6[/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.